RANCANG BANGUN SISTEM INFORMASI PEMESANAN MAKANAN PADA KAFE YXZ DI DEPOK - Arief, Trisna Nur; Setiawan, Setiawan; Setiady, Teddy (JURNAL LENTERA ICT, 2025)
The rapid development of information technology has influenced various sectors of life, including the culinary sector. Restaurants, as food service providers, are required to utilize technology to improve operational efficiency and customer convenience. A restaurant food ordering system based on mobile phones makes it easier for customers to view the menu, select their orders, and confirm them without having to wait for a waiter. This system is designed using the Android platform with a simple and user-friendly interface. With this system, customers can order food efficiently, minimize errors in order recording, and reduce waiting time. The results of this study indicate that using a mobile phone-based food ordering system can increase customer satisfaction and provide added value for restaurants in terms of service. This system also has the potential to be integrated with digital payment systems to support the process faster and safer transactions. It is hoped that this innovation can be an initial step in the digital transformation of the culinary sector, particularly in restaurant services.